2012
DOI: 10.1007/s13337-012-0114-z
|View full text |Cite
|
Sign up to set email alerts
|

Viruses Occurring in Onion Crop in Amasya Province, the Major Onion Producing Region in Turkey

Abstract: Amasya is the greatest onion producing area in Turkey. Onion fields from Amasya region were surveyed for virus diseases in 2009-2011 and tested for the presence of the most important onion viruses such as Onion yellow dwarf virus (OYDV), Iris yellow spot virus (IYSV), Leek yellow stripe virus (LYSV), Shallot latent virus (SLV) and Garlic common latent virus (GCLV). The presence of virus diseases and their identification was ascertained through symptom observation in the fields, sap transmission to hosts, and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…Therefore, the low LYSV infection rate could most likely be attributed to the absence of aphid vectors on fields that limit the spread of LYSV. Low LYSV infection rates on onions were also reported on surveys in other regions of Turkey and other countries (Dovas and Vovlas 2003, Fidan 2010, Sevik and Akcura 2013, Vučurović et al 2017). However, infection rate of 60.1% was observed in Tehran region of Iran (Shahraeen et al 2008).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Therefore, the low LYSV infection rate could most likely be attributed to the absence of aphid vectors on fields that limit the spread of LYSV. Low LYSV infection rates on onions were also reported on surveys in other regions of Turkey and other countries (Dovas and Vovlas 2003, Fidan 2010, Sevik and Akcura 2013, Vučurović et al 2017). However, infection rate of 60.1% was observed in Tehran region of Iran (Shahraeen et al 2008).…”
Section: Discussionsupporting
confidence: 58%
“…So, RT-PCR was only performed on all samples against LYSV. Previous studies identified OYDV and CMV on Allium species cultivated in other regions of Turkey (Fidan 2010, Sevik and Akcura 2013, Tuzlalı et al 2016.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In India, OYDVoccurs in epiphytotic proportion (Ahlawat and Varma 1997) and the highest incidence of OYDV infection was reported from Maharashtra, Gujarat and Madhya Pradesh (Gawande et al 2013). It has also been reported from several countries, including Argentina, Turkey, Iran, Serbia, Poland, Italy, Nepal, Sudan, Greece, Egypt, Brazil, Czech Republic and in the USA (Sevik and Akcura 2013;Baghalian et al 2010;Bagi et al 2012;Chodorska et al 2014;Manglli et al 2014;Majumder and Johari 2014 ). Here, we present the complete genome sequence of the OYDV isolate RR1 from onion (Allium cepa) in India.…”
Section: Introductionmentioning
confidence: 69%
“…It was first reported in Turkey in leek planted in Marmara region (Korkmaz and Cevik, 2009). Later on, the virus was shown to infect leek, onion, and garlic grown in East Mediterranean, Amasya province, and Marmara region of Turkey (Fidan and Baloğlu, 2009;Fidan, 2010;Sevik and Akcura, 2013;Tuzlalı, 2018;Sarı et al, 2020).…”
Section: Introductionmentioning
confidence: 99%